Pengaruh Human Capital dan Budaya Organisasi terhadap Kinerja Karyawan di PT. Hutahaean Pabrik Tapioka Desa Pintu Bosi Kecamatan Laguboti - Sitorus, Widya Elizabeth; Siregar, Onan Marakali (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to analyze the influence of human capital and organizational culture on employee performance at PT. Hutahaean Tapioka Factory Pintu Bosi Village, Laguboti District. The research method used in this study is quantitative research with a descriptive approach. The population in this study is employees of PT. Hutahaean Tapioca Factory Pintu Bosi Village, Laguboti District which totaled thirty seven people. The data collection method used in this study is primary data obtained by distributing questionnaires while secondary data is obtained through literature studies. The results of the research conducted show that human capital variables and organizational culture have a partial and significant effect on employee performance. The coefficient value also shows the relationship between human capital and organizational culture to strong employee performance with an R value of 0.589 or 58.9%. The value of Adjusted R Square is also known that human capital and organizational culture on employee performance amounted to 34.7% while the remaining 65.3%, influenced by other variables that was not discussed in this study.